Analisis Faktor-Faktor Penghambat Belajar Membaca Permulaan Pada Siswa Kelas I UPT SPF SD Inpres Jongaya Kecamatan Tamalate - Resqita Mautiah Anshar; Muhammad Akhir; Besse Syukroni (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The main problem in the research is identifying the factors that hinder the initial reading learning process for class I UPT SPF SD Inpres Jongaya students, Tamalate District. The research aims to analyze the factors inhibiting beginning reading in class I UPT SPF SD Inpres Jongaya, Tamalate District. The type of research is qualitative research with descriptive methods. Researchers collect data through observation, interviews and documentation. The subjects in the research were 5 students in class I UPT SPF SD Inpres Jongaya, Tamalate District, who were classified as having low initial reading ability. The results of the research show that there are two factors that hinder the initial reading learning process at UPT SPF SD Inpres Jongaya, Tamalate District, namely internal factors and external factors. Internal factors include children's lack of memory, children's slow understanding of learning, students' lack of attention to learning in class, excessive pressure on children, and children's lack of motivation and interest. External factors include lack of parental attention, lack of learning media available at home, lack of teacher skills, students never attending PAUD, lack of focus on reading activities at students' previous school (TK), limited time and attention of the community as well as the use of gadgets and playing excessive online games. Thus, it can be concluded that these factors hinder the initial reading learning process for class I students at UPT SPF SD Inpres Jongaya, Tamalate District.